40‐5: Invited Paper: High Frame‐Rate 1" WUXGA OLED Microdisplay and Advanced Free‐Form Optics for Ultra‐Compact VR Headsets. Issue 1 (30th May 2018) - Wartenberg, Philipp; Buljan, Marina; Richter, Bernd; Haas, Gunther; Brenner, Stephan; Thieme, Mike; Vogel, Uwe; Benitez, Pablo
Abstract : This paper describes two key components for VR: optics and high‐resolution microdisplay. Within the European‐funded project LOMID a new microdisplay with WUXGA resolution for an ultra‐compact optics has been developed. The new optics enables very high resolution VR by using four WUXGA displays at the same time in a particularly compact design.